INFLUÊNCIA DO CONTEÚDO DE MATÉRIA SECA E REGULAGENS DE UMA COLHEDORA DE FORRAGEM NOS TAMANHOS DE FRAGMENTOS E NA DENSIDADE DA SILAGEM DE PLANTA INTEIRA DE DOIS HÍBRIDOS DE MILHO (Zea mays L.) 2008 - Garbuio, Paulo William (2008)
In Brazil, the best dairy farm efficiency levels are obtained in the cities of Castro and Carambeí, State of Paraná. This efficiency was reached due to the animal genetics and the feed management, where the corn whole plant silage has been wide used. To the highest profit of the silage, some stages must be considered. The main stages are the selection of the forage harvest point, the plants chopping and the silo compaction. This work aims to present the possible interactions between the factors: plants water content, forage harvester setup with the plant particles size and de silage compaction process. The two corn hybrids (SPEED e 2B688) studied had been harvested in five times (105, 108, 112, 118, 123 seeding after days). In every harvest time it was evaluated the relative participation of the plant components, the dry matter, the fresh mass and grains yields and the milk line, to each corn hybrid. To the silage chopping evaluation, 120 plants were harvested and chopped with a forage harvest using three setups. The chopped material was used to the particles size determination and later submitted to the compaction process. To the grains and fresh mass yield, and milk line evaluation, the treatment was the harvest times, with five replications. The analysis of variance applied completely randomized experimental design. It was analyzed the correlation between the dry matter and the milk line. The particle size and silage bulk density analysis was carried through a factorial 5x3 design with four replications, where the first factor had been the harvest times, and the second the three forage harvester setups. Only one hybrid presented a high correlation between the milk line and the dry matter, showing the milk line method to be not a good way to evaluate the dry matter of plants, and behaves by different ways according the corn hybrid. To the grains yield, the SPEED hybrid showed difference, between the first and the three last harvest times. The compaction test showed a high correlation between the green mass density with the plant maturation, where plants with highest dry matter content make the compaction more difficult. Differences was verified to the silage bulk density according to the forage harvest setup, when the chopped material in the setup to theoretical cut length (TCL) of 2mm had easy compaction that the setups to TCL of 6,5 and 11 mm. To the particle size, when evaluated the hybrid 2B688, the different plant dry matter levels had not effects in the average particle size. However, to the hybrid SPEED, the particles size reduced with the plants maturation. To the evaluated materials, the dry matter content, as well as the forage harvest setups affected the green mass bulk density and the real particles size. The forage harvest setup changes resulted in different particle sizes that the informed by the manufacturer.